Perception of social tourism and recreation in the elderly as a tool to improve the quality of life in the canton of Latacunga - Cabezas Mejía, Edison Damián; Cristina Maribel, Nasimba Suntaxi; Torres Santamaría, Johana; Carrasquero Carrasquero, Ender (mktDESCUBRE; Vol 1 No 1 (2020): InnovaEc 2019 Special Edition Congress, 2020)
Encouraging the adoption of a culture of quality in tourist accommodation companies has become a primary objective for the Ministry of Tourism, due to the accelerated growth of tourism and the great global competition, for this reason it is essential that companies that provide services understand the importance of acquiring knowledge, skills and abilities that allow the staff to offer quality in the attention they provide, consequently the present research topic provides a consolidation of information referring to quality principles focused on customer service applied to the accommodation facilities of the Pujilí canton, this project was developed through the initial system of organizational management (SIGO-Ecuador) that is currently used to diagnose quality in tourist establishments, in this same sense an international tool known as HotelQual was used To measure the perception of the guests, in this way the final result showed that the quality of the accommodation service directly influences the perceptions of the same, so it is necessary to improve the quality in the accommodation establishments so that in this way the clients' perceptions are positive and their total satisfaction is achieved.